Vibroacoustics of insects: a meta-analysis and the first expedition into the hitherto unknown vibratory world of the fall armyworm - Turchen, Leonardo Morais (2021)
Vibratory sensing and communication in insects has been researched for decades, and this sensory modality has recently garnered popularity in the scientific community. There is an increasing body of evidence demonstrating (or suggesting) the relevance of solid-borne vibrations in a wide range of insect behaviors, from passive cue detection to complex communication signals. Despite growing awareness of this sensory modality, many questions remain unanswered. My Ph.D. dissertation was divided into two chapters to address some of these issues. First, a systematic survey with meta-analyses was performed to identify knowledge gaps and biases in these research topics. The survey tracked 831 papers during the last 75 years, which exhibited exponential growth since the 1990s, and reported 17 insect orders associated with vibratory events. In these studies, three prominent biases were detected: i) prevalence of studies on Hemiptera, Hymenoptera, and Coleoptera; and ii) a focus on adults, with far less attention to juveniles; and iii) on reproductive behaviors, with less attention to other behavioral contexts. Other gaps were identified, such as a lack of study on most insects' vibration landscapes and a lack of research on the processes employed by insects to perceive and process vibrations, both of which require more investigation. In the second chapter, an experiment was conducted to characterize relevant vibrations in the landscape of a caterpillar using spatial analysis, and, subsequently, to test whether fall armyworm larvae can detect and respond to vibrations from the wind, raindrops, conspecifics, and heterospecifics (a predatory stinkbug). The results show that vibrations from abiotic and biotic stimuli were distinct from background noise, except those produced by the crawling of 1st instar larvae. Moreover, the spatial analysis revealed that vibrations exhibit contrasting distribution patterns in the leaf depending on their origin. Vibrations caused by simulated wind and raindrops were more widely spread across the leaves. In contrast, the vibrations produced by fall armyworm crawling or stinkbug walking were concentrated on some leaf regions. Our findings also supported the hypothesis that fall armyworm larvae are able to detect abiotic and biotic vibrations and respond to them. Caterpillars exposed to wind and rain stimuli behaved differently than unexposed caterpillars, regardless of instar. Caterpillars exposed to wind responded with a greater transition from crawling to touching around, whereas caterpillars exposed to raindrops responded with a greater transition from crawling to resting. Caterpillars exposed to biotic stimuli did not exhibit a consistent response among instars, as first instars did not respond to the approach of a conspecific or a predator, whereas caterpillars from second to fifth instars responded. When approached by a conspecific, caterpillars spend less time feeding and more time crawling, touching around, or resting, and eventually produce defensive behaviors. In contrast, caterpillars exposed to predators spend more time freezing, feeding, and resting, eventually exhibiting other defensive behaviors. In conclusion, these findings shed new light on the vibroacoustic landscapes of insects. First, they identify major gaps in the literature, indicating that future studies should focus on a larger variety of orders and higher taxa (i.e., genera, families, and species), including the significance of vibration in various adaptive contexts and how both adults and juveniles (i.e., eggs, larvae/nymphs, and pupae) use vibrations. These findings also provide new insights into a caterpillar's vibratory landscape on a leaf scale utilizing spatial analysis, revealing that complex vibratory environments exist even on a small scale. It also supports the hypothesis that fall armyworm larvae can detect and respond to both abiotic and biotic vibrations in order to survive. Keywords: Behavior. Biotremology. Caterpillar. Insects. Predatory stinkbug. Solid-borne vibrations. Spatial distribution. Vibrational communication.